TNFR1-deficient mice display altered blood pressure and renal responses to ANG II infusion - Chen, Chun Cheng Andy (American Physiological Society, 2010)
The hypothesis that TNF receptor 1-deficient (TNFR1(−/−)) mice display blood pressure (BP) and renal functional responses that differ from wild-type (WT) mice was tested in an angiotensin II (ANG II)-dependent model of hypertension. Basal systolic BP (SBP), mean arterial pressure, diastolic BP, heart rate (HR), and pulse pressure were similar in WT and TNFR1(−/−) mice. Infusion of ANG II for 7 days elevated SBP to a greater extent in TNFR1(−/−) compared with WT mice; pulse pressure was also elevated in TNFR1(−/−). HR decreased in TNFR1(−/−) mice infused with ANG II, an effect prominent on day 1. Basal urinary albumin excretion was similar in WT and TNFR1(−/−) mice but was higher in TNFR1(−/−) in response to ANG II infusion. Water intake and urine volume were increased by ANG II infusion; this increase was higher in TNFR1(−/−) vs. WT mice, whereas body weight and food intake were unaffected. Baseline creatinine clearance (Ccr), urinary sodium excretion, and fractional excretion of sodium (FE(Na)%) were similar in vehicle-treated WT and TNFR1(−/−) mice. ANG II infusion for 7 days increased Ccr and filtered load of sodium in TNFR1(−/−) but not WT mice, whereas it elicited an increase in FE(Na)% and urinary sodium excretion in WT but not TNFR1(−/−) mice. ANG II also inhibited renal TNFR1 mRNA accumulation while increasing that of TNFR2. These findings indicate deletion of TNFR1 is associated with an exacerbated SBP response, decrease in HR, and altered renal function in ANG II-dependent hypertension.